THE IMPACT OF LUNAR SIGHTING DISCREPANCIES ON THE BEGINNING AND END OF RAMADAN FASTING: A COMPARATIVE FIQH ANALYSIS AND THE ROLE OF AI IN RESOLVING DIFFERENCES - Abdulrahman, Manswab Mahsen (Jurnal Syariah, 2025)
The beginning and end of Ramadan have traditionally been determined by physically sighting the crescent moon. Despite this long-established practice, differences in lunar visibility across regions frequently result in varying start and end dates for fasting. These variations often create confusion among Muslim communities, sometimes leading to disagreement among scholars and worshippers regarding the correct time to observe Ramadan. This study adopts a comparative fiqh approach, analysing the perspective of classical and contemporary jurists on moon-sighting methodologies. It also explores how modern artificial intelligence (AI) technologies could contribute to minimizing these differences. Using a qualitative and comparative methodology, the research draws upon primary and secondary fiqh sources, juristic opinions, and recent studies on astronomical calculation. The findings of this research highlight three legitimate methods for confirming the commencement of Ramadan; sighting the crescent moon (ru’yah al-hilāl), completing thirty days of Sha’ban (ikmāl Sha’ban), and estimating the crescent moon in cloudy conditions (ḥisāb). Furthermore, the determination of Ramadan’s start and end dates has been a persistent source of debate among Muslim communities worldwide due to inconsistencies in moon sighting (ikhtilāf al-maṭāli’), particularly between proponents of global sighting (ru’yah al-’alam) and local sighting (ru’yah al-maḥallī). Each region follows its own sighting. In response to these challenges, AI-equipped drones have been introduced to enhance the detection of the Ramadan crescent moon by providing accurate predictions and identifying optimal locations for moon sighting.